The Appsmart Learning Application Based on the PBL Model Assisted by Articulate Storyline 3 Material on Earth and The Universe - Agung Ayu Komang Mia Anjali; I Gede Margunayasa; Ni Wayan Rati (Universitas Pendidikan Ganesha, 2023)
The decline in students' science learning outcomes was due to the need for more application of learning models that fit students' needs. This study aims to develop an Appsmart learning application based on the PBL model assisted by Articulate Storyline 3, which discusses Earth and the Universe material for fifth-grade elementary school. This research belongs to the type of development research which was developed using the ADDIE model. The ADDIE development model comprises five stages: analysis, design, development, implementation, and evaluation. The subjects involved in this study were four experts, three teachers, and 28 students. Data collection in this study was carried out using test and questionnaire methods, with research instruments in the form of evaluation tests and expert test questionnaires. The data obtained in the study were then analyzed using descriptive analysis techniques and the mean formula to determine the level of feasibility and practicality. The results of the application feasibility test reached 4.67, and the material feasibility test reached 4.65 so that it could be declared fit for use. The results of the practicality test for teachers and students reached 4.87 and 4.97, which were stated to be practical to implement. The significance value of the t-test shows the number 0.00. Based on these results, there is a significant influence from the PBL model-assisted Appsmart learning application assisted by Articulate Storyline 3 with an understanding of the science concept of Earth and the Universe material for fifth-grade students.